2011
DOI: 10.1021/ma200076q
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity of Graphite Oxide-Based Suspensions in PDMS

Abstract: International audienceThe visco elastic behavior of graphite oxide-loaded PDMS suspensions showed, at low frequencies, a dominant elastic behavior with the appearance of a secondary plateau above 1.5 wt %. Within the investigated concentrations, such behavior was not observed for the graphite and functionalized graphite oxide/PDMS suspensions. This low percolation threshold of GO sheets was attributed to a macroscale aggregation. Furthermore, the critical strain (transition between the linear and nonlinear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…This agreed with the findings of a previous study that used the same type of graphene [63]. After mild oxidation with KMnO4, a prominent diffraction peak appeared at 2θ = 11.16°, reflecting the interlayer spacing of 0.79 nm (according to Bragg's law [64,65]). The small peak at 2θ = ~26° suggests the existence of unoxidized graphene [66].…”
Section: Xrd Analysissupporting
confidence: 91%
“…This agreed with the findings of a previous study that used the same type of graphene [63]. After mild oxidation with KMnO4, a prominent diffraction peak appeared at 2θ = 11.16°, reflecting the interlayer spacing of 0.79 nm (according to Bragg's law [64,65]). The small peak at 2θ = ~26° suggests the existence of unoxidized graphene [66].…”
Section: Xrd Analysissupporting
confidence: 91%
“…For W i > 1, intrinsic viscosity only slightly decreases with increasing W i; these results are similar to recently published experimental data on dilute solutions of graphene oxide 36 and graphite oxide suspensions in polydimethylsiloxane (PDMS). 37 Tesfai et al 36 showed that the exponent of the power law relationship between relative viscosity and Wi is within −0.1 to −0.5 while our Figure 9 shows an exponent of ∼−0.25. This also indicates the larger W i value used in Figure 8 yields experimentally relevant viscosity values.…”
Section: Resultsmentioning
confidence: 50%
“…In previous work, there are different mechanisms for the shear thinning of nanoparticle suspensions and composites [35][36][37], for instance the shear induced aggregation and de-aggregation in multiwall carbon nanotube (MWNT)/epoxy suspensions [37]. In this work, the slopes of η versus γ at low shear rates are about -0.9, -1.5 and -1.2 for OMMT/SO, GO/SO and Kaolin/SO suspensions, respectively.…”
Section: Nonlinear Rheological Properties Of Plate-like Particle Suspmentioning
confidence: 65%